Local endemism and ecological generalism in the assembly of root‐colonizing fungi. Issue 1 (3rd November 2021) - Maciá‐Vicente, Jose G.; Popa, Flavius
Abstract: Root‐colonizing fungi form species‐rich assemblages with key functions in principal ecosystem processes, making them prospectively important players in conservation and applied ecology. Harnessing the processes and services they drive requires a better understanding of their patterns of diversity and community structure, and how these link to function. Here, we search for possible adaptations to contrasting environmental and host conditions, indicative of participation in habitat‐specific processes. We surveyed heathland and grassland habitats across a latitudinal gradient in Western Europe, using a spatially explicit design to assess community variation at scales from centimeters, to thousands of kilometers. Root‐associated fungi assemble into strongly site‐specific communities irrespective of habitat type, shaped by environmental factors and spatial distance operating at different scales, but also by a high level of endemism, likely to be determined by local stochastic processes such as drift and dispersal limitation at short distances. Despite the high site specificity in communities, they are dominated everywhere by a core set of lineages with little preferences toward habitat conditions or host phylogeny. Our results suggest a convergent evolution across phylogenetically distant lineages toward the root‐colonizing habit, and a functional redundancy in strategies for habitat colonization and host interaction. Further efforts are needed to integrate functional trait composition in future community ecology studies of root‐colonizing fungi.